Urban Hydrogeology Studies - Gogu, C. Radu (2022)
Urbanization worldwide is a pervasive phenomenon of our time, and sustainable urban development is one of the greatest challenges faced by the contemporary world. The subsurface plays a range of roles in such developments through the complex processes of urbanization, including building development, constructing roads, and providing water supplies, drainage, sanitation, and even solid waste disposal.Urban groundwater problems are usually predictable; however, they are not predicted early enough. During recent decades, progressive advances in the scientific understanding of urban hydrogeological processes and the groundwater regimes of a substantial number of cities have been documented. This extensive array of subsurface challenges that cities have to contend with lies at the core of the sustainability of the urban water cycle. This is threatened by the increasing scale and downward extent of urban subsurface construction, including utilities (cables, sewage, and drainage), transportation (tunnels, passages), and storage (cellars, parking lots, and thermal energy). The cumulative impact of this subsurface congestion on the surrounding geology, and especially on the groundwater system, has to be constantly studied and addressed.In this volume, key connections amongst urban hydrogeology activities are identified as being consistent with scientific results and good practices in their relationship to subsurface data and knowledge on subsurface systems. The volume supports a useful dialogue between the providers and consumers of urban groundwater data and knowledge, offering new perspectives on the existing research themes.